Ataxin-3 Links NOD2 and TLR2 Mediated Innate Immune Sensing and Metabolism in Myeloid Cells - Chapman, Thomas P.; Corridoni, Daniele; Shiraishi, Seiji; Pandey, Sumeet; Aulicino, Anna; Wigfield, Simon; do Carmo Costa, Maria; Thézénas, Marie-Laëtitia; Paulson, Henry; Fischer, Roman; Kessler, Benedikt M.; Simmons, Alison (Frontiers in Immunology, 2019)
The interplay between NOD2 and TLR2 following recognition of components of the bacterial cell wall peptidoglycan is well established, however their role in redirecting metabolic pathways in myeloid cells to degrade pathogens and mount antigen presentation remains unclear. We show NOD2 and TLR2 mediate phosphorylation of the deubiquitinase ataxin-3 via RIPK2 and TBK1. In myeloid cells ataxin-3 associates with the mitochondrial cristae protein MIC60, and is required for oxidative phosphorylation. Depletion of ataxin-3 leads to impaired induction of mitochondrial reactive oxygen species (mROS) and defective bacterial killing. A mass spectrometry analysis of NOD2/TLR2 triggered ataxin-3 deubiquitination targets revealed immunometabolic regulators, including HIF-1α and LAMTOR1 that may contribute to these effects. Thus, we define how ataxin-3 plays an essential role in NOD2 and TLR2 sensing and effector functions in myeloid cells.